(untitled) (Journal of actual problems of jurisprudence, 2019)
The article deals with the concept of religious extremism and the way to combat it. Also describes a comprehensive analysis of the legal framework of the legal and regulatory framework of legislation passed by the Republic of Kazakhstanthat provides security of the people